Silenced by evidence: Evidentiary patriarchy, statutory rape, and judicial bias in Indonesia - Nuqra Ramikhudoeva (Priviet Social Sciences Journal, 2026)
Despite the existence of comprehensive child protection legislation, sexual violence against minors in Indonesia continues to face significant barriers to justice. This article argues that the rigid application of the principle of unus testis nullus testis under Article 185 (2) of the Indonesian Criminal Procedure Code or Kitab Undang-Undang Hukum Acara Pidana (KUHAP) can undermine the protective purpose of child protection law in cases of child sexual violence. Using a normative juridical method combined with socio-legal analysis and feminist jurisprudence, this study examines the Parigi District Court Decision Number 55/Pid.Sus/2024/PN PRG (I Made Darsa) and its subsequent reversal by the Supreme Court and its subsequent reversal by the Supreme Court. This article develops the concept of evidentiary patriarchy as an analytical framework to explain how formally neutral evidentiary standards may disproportionately disadvantage child victims by privileging corroborative certainty over the realities of trauma, coercion, and unequal power relations. The findings demonstrate that the Parigi District Court’s acquittal reflected not only concerns regarding evidentiary sufficiency but also an interpretative approach that weakened the lex specialis protections afforded by child protection law and obscured the legal irrelevance of consent in statutory rape cases involving minors. In contrast, the Supreme Court adopted a more contextual and child-centered interpretation that aligned more closely with substantive justice principles. This study concludes that improving access to justice for child victims requires not only legal protection but also an evidentiary interpretation that is sensitive to vulnerability, power imbalance, and the protective objectives of child protection legislation.